Modelos de ciudadanía: discursos sobre roles femeninos en la legislación chilena - Verónica Gómez-Urrutia (Universidad Autónoma del Estado de México, 2014)
A central theme in gender-sensitive citizenship research is the need to reorganize the current social and political institutions so as to include reproductive work i.e, domestic and care work in the domain of duties of the citizen. This article examines this topic from the perspective of social representations on mens and womens contribution to society contained in four pieces of the Chilean legal discourse that specifically address issues of family organization and childcare. Methodologically, the paper is based on the discursive analysis of the written records of the debates held in the Congress on these legal initiatives, complemented with semi-structured interviews with MPs and government officials. From this analysis it is possible to conclude that, despite important advancements, womens citizenship is still represented as contributing to society mainly through care and, more recently, through their contribution towards overcoming poverty.